If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.60x + 0.05(12 + -1x) = 0.10(-49) 0.60x + (12 * 0.05 + -1x * 0.05) = 0.10(-49) 0.60x + (0.6 + -0.05x) = 0.10(-49) Reorder the terms: 0.6 + 0.60x + -0.05x = 0.10(-49) Combine like terms: 0.60x + -0.05x = 0.55x 0.6 + 0.55x = 0.10(-49) Multiply 0.10 * -49 0.6 + 0.55x = -4.9 Solving 0.6 + 0.55x = -4.9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6' to each side of the equation. 0.6 + -0.6 + 0.55x = -4.9 + -0.6 Combine like terms: 0.6 + -0.6 = 0.0 0.0 + 0.55x = -4.9 + -0.6 0.55x = -4.9 + -0.6 Combine like terms: -4.9 + -0.6 = -5.5 0.55x = -5.5 Divide each side by '0.55'. x = -10 Simplifying x = -10
| 2(12)+2x=2(x-2)+2(16) | | 4n+2+4=-6 | | 2(3x-3)+2(x-3)=(2x-1)+(2x-1)+2x | | x^6-47x^3-8=0 | | 3c-4c+1=5+2+3 | | 4y+3y=63 | | 3c+4c+1=5+2+3 | | (x+55)+(3x-5)=180 | | 0.5d=3 | | 2(3x-3)+2(x-3)=(2x-1)+(2x+1)+2x | | 7=-v-3+6 | | 4(b-2)=(5-b) | | (x+55)+(3x-5)=90 | | 4r^2-r=0 | | 6,5x-9=10,5 | | 2.5d=3 | | 2=5r-3r | | 4q+8=5y | | 6x-2(x+3)=5x-1(+2) | | -6x+5(5x+12)=-168 | | 5y+12x+6=0 | | p-4=-9+9 | | 26-(3x+2)= | | 5x-17=2x+10 | | 22=11k | | 14-x=48 | | 2c-3+9d+7-6d= | | x+(x-26)=180 | | 1h+1+2h+1=6h+6-1h+2 | | 5+9y=5y+5 | | x(y-3)=40 | | 5x+4=23 |